SOIL ORGANIC MATTER CONTENT AND ITS EFFECT ON PRODUCTIVITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article studies the content of soil organic matter and its impact on agricultural productivity. The article analyzes the main sources of organic matter, its functions in the soil, and its specific effects on productivity. The results show that a decrease in the content of organic matter in the soil significantly reduces productivity, and also negatively affects the water-holding capacity, structure, and nutrient reserves of the soil. The article also suggests methods for increasing organic matter reserves.